2006
DOI: 10.1253/circj.70.1208
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Neurohumoral Factors are Associated With Left Ventricular Remodeling and Poor Prognosis in Rats With Monocrotaline-Induced Pulmonary Arterial Hypertension

Abstract: ulmonary arterial hypertension (PAH) is a disorder induced by various causes, such as collagen or pulmonary obstructive/restrictive disease-associated vasculopathy, pulmonary artery embolism, hypoxia, and inflammatory diseases, as well as genetic abnormalities. 1,2 Although the etiology of PAH is diverse, the essential pathophysiology is an elevation in the resistance of the pulmonary arteries characterized by vascular remodeling and smooth muscle spasm with continuous progression of luminal obliteration. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
5
28
0
Order By: Relevance
“…19 In this previous study, only a nonsignificant trend toward higher ECV at the septum and LV lateral wall was observed. 25 In the current model, ECV was again significantly higher at the RV insertion points, showing a good correlation with the severity of PH, but differences in ECV at the septum and LV lateral wall were also significant, reflecting an inherent damage at the LV. Pressure overload and, remarkably, significant lung parenchymal damage 26 seem to induce greater myocardial fibrosis than volume overload.…”
Section: Discussionsupporting
confidence: 46%
“…19 In this previous study, only a nonsignificant trend toward higher ECV at the septum and LV lateral wall was observed. 25 In the current model, ECV was again significantly higher at the RV insertion points, showing a good correlation with the severity of PH, but differences in ECV at the septum and LV lateral wall were also significant, reflecting an inherent damage at the LV. Pressure overload and, remarkably, significant lung parenchymal damage 26 seem to induce greater myocardial fibrosis than volume overload.…”
Section: Discussionsupporting
confidence: 46%
“…Crotalaria spectabilis that can be administered by intraperitoneal, subcutaneous or intravenous injection to induce right ventricular dysfunction and HF within 4-6 weeks [30,299]. Current hypotheses of the pathogenesis of MCTinduced pneumotoxicity suggest that MCT is transformed in a bioactive pyrrole metabolite in the liver and is then transported by red blood cells to the lung, where it initiates endothelial injury.…”
Section: Monocrotaline (Mct) Is a Plant Toxin Derived Frommentioning
confidence: 99%
“…It is reported that carvedilol improves survival rate in MCT-induced PAH rats. 21 Therefore, we need to perform further study to clarify the effect of arotinolol on the long-term outcome.…”
Section: Study Limitationsmentioning
confidence: 99%